2015
DOI: 10.1016/j.jvs.2014.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Year Mortality After Venous Thromboembolism: A Population-Based Cohort Study

Abstract: The data once again emphasized that AKI following endovascular aortic repair is an infrequent but morbid complication. For both open and endovascular repair of the abdominal and thoracic aorta, acute kidney injury portends a worse short and long-term outcome even if the patient does not become dialysis dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 0 publications
0
89
0
3
Order By: Relevance
“…This would make more meaningful the observation of a much worse 30-year prognosis in individuals who had experienced PE after DVT. 41 A limitation of the current investigation is that it was a single-center survey, although the results, obtained in an elderly high-risk cohort hospitalized in a department of internal medicine, are robust, as ROC analyses, data on predictive values, and likelihood ratios confirmed. It could be argued that the D-dimer cutoff, used to restrict the number of individuals in whom MDCT should be conducted, tends to be higher in elderly people and in individuals with renal dysfunction, as recently emphasized, 42 although in the present study, using the cutoff of 500 ng/mL increased the pretest probability of diagnosing PE in individuals with a low to intermediate level of probability.…”
Section: Discussionmentioning
confidence: 88%
“…This would make more meaningful the observation of a much worse 30-year prognosis in individuals who had experienced PE after DVT. 41 A limitation of the current investigation is that it was a single-center survey, although the results, obtained in an elderly high-risk cohort hospitalized in a department of internal medicine, are robust, as ROC analyses, data on predictive values, and likelihood ratios confirmed. It could be argued that the D-dimer cutoff, used to restrict the number of individuals in whom MDCT should be conducted, tends to be higher in elderly people and in individuals with renal dysfunction, as recently emphasized, 42 although in the present study, using the cutoff of 500 ng/mL increased the pretest probability of diagnosing PE in individuals with a low to intermediate level of probability.…”
Section: Discussionmentioning
confidence: 88%
“…Mortality from VTE has been estimated at 8 years to be between 12% and 50%. 42 44 Despite this potentially deadly complication, many surgeons have been reluctant to use pharmacologic prophylaxis in the setting of liver resection, citing risk of postoperative bleeding, impaired postoperative liver function, and "auto-anticoagulation." [45][46][47] Recent publications, however, have demonstrated that the rate of pulmonary embolus after liver resection is 6% and the rate of VTE approaches that of other abdominal operations for malignancy.…”
Section: Post-hepatectomy Venous Thrombosis/thromboembolismmentioning
confidence: 99%
“…VTE is considered to be a chronic, recurrent disease and, despite anticoagulant and thrombolytic therapy [4,5], roughly one-third of patients experience recurrent VTE within 10 years [1], peaking at 6 months after the index VTE [2]. Importantly, the mortality risk remains increased up to 30 years after the index VTE [6]. Therefore, recurrent VTE is responsible for substantial co-morbidities and healthcare costs [7], and identifying strategies to reduce the burden of recurrent VTE is crucial.…”
Section: Introductionmentioning
confidence: 99%